Islamic Finance As A Catalyst For National Economic Development In OIC Member States - Muh Ibnu Sholeh; Irom Gambhir Singh (International Journal of Economics and Development, 2025)
This study explores the role of Islamic finance as a catalyst for national economic development across selected member states of the Organization of Islamic Cooperation (OIC). Employing a mixed-method approach, the research combines quantitative data from 2010 to 2022 including GDP growth, Islamic Finance Development Index (IFDI), financial inclusion, and poverty rates with qualitative case studies from Malaysia, Indonesia, the United Arab Emirates, Saudi Arabia, and Pakistan. The findings indicate that Islamic finance contributes significantly to three pillars of sustainable development: economic growth, financial inclusion, and poverty alleviation. Instruments such as sukuk, Islamic microfinance, digital zakat, and productive waqf models are shown to enhance access to capital, promote ethical investment, and support grassroots development. The success of these initiatives is strongly correlated with supportive public policy, a robust Islamic banking ecosystem, and digital transformation through sharia-compliant fintech. Furthermore, cross-border harmonization of regulations and fatwas is crucial to ensure market integration among OIC countries. The study concludes that Islamic finance, rooted in ethical and inclusive principles, is not merely an alternative financial system but a transformative tool for achieving inclusive and sustainable economic development